A COMPONENT OF PROFESSIONAL COMMUNICATIVE COMPETENCE IN ENGLISH IS PROFESSIONAL ENGINEERING KNOWLEDGE (Journal of Universal Science Research, 2023)
This article about methods and tools of knowledge of a component of professional communicative competence in English is professional engineering knowledge. Summarizing some of the progress made in education reform over the past decade, scholars recognize the need for large-scale modernization to improve quality and accessibility to meet society's demands.